Development, validation and acceptability of a newly developed nutrition resource kit for at-risk and malnourished elderly in health clinics setting - Noor Azam, Iman Nabihah; Hamirudin, Aliza Haslinda; Harith, Sakinah; Md Aris, Mohd Aznan; Abd. Aziz, Karimah Hanim; A Rashid, Nurul Syaireen (Universiti Putra Malaysia Press, 2022)
Introduction: The elderly population is highly vulnerable to malnutrition, including those in the community. The use of nutrition education as part of nutrition intervention is able to improve their nutritional status. Hence, provision of a nutrition resource kit addressing the needs of at-risk and malnourished elderly would be advantageous. This research aimed to develop, validate and evaluate the acceptance of a newly developed nutrition resource kit, which served as an educational material among at-risk and malnourished elderly in Malaysian health clinics. Methods: This study was conducted in three phases: Phase I comprised of qualitative needs assessment to identify the types of nutrition resource kit needed; Phase II was the development and validation of the nutrition resource kit; while Phase III was acceptance evaluation, which involved individual in-depth interview and triangulation. Results: An A5-sized booklet with incorporation of an educational video in a QR code was developed. Both printed material and educational video had excellent content and face validity. Suggestions by experts and elderly from validation were considered and revision was done accordingly. Acceptance evaluation revealed four themes: 1) positive acceptance, 2) elderly-friendly, 3) valuable, and 4) individual preference. Triangulation data revealed that all elderly positively evaluated both resources. Additional suggestions given by elderly were considered for improvement. Conclusion: This newly developed nutrition resource kit, both in the printed and electronic format, was well-accepted among the at-risk and malnourished elderly. It could be used as an important reference for the elderly, especially those attending health clinics, in treating and preventing malnutrition.